METHODOLOGICAL APPROACH TO FORMING TEACHERS' EFFICIENT COMMUNICATION WITH STUDENTS AT RISK OF SCHOOL DROPOUT - Katy KAKOON (Moldova State University, 2020)
This article is dedicated to the specific methodology on forming the communication skills of teachers who teach students at risk of school dropout. The quality of teacher training in effective didactical communication must become an integral and compulsory part of teacher training. They will support all students to reduce the risk of school dropout. These teachers need to become professionals who are always available to students, demonstrate openness and flexibility for communication / networking with students, have the ability to resolve conflicts, developing learning motivation of students at risk of school dropout.   ABORDARE METODOLOGICĂ ÎN FORMAREA COMUNICĂRII EFICIENTE A CADRELOR DIDACTICE CU ELEVII EXPUȘI RISCULUI DE ABANDON Prezentul articol este dedicat metodologiei specifice de formare a abilităților de comunicare a profesorilor care învață elevii în situații de risc de abandon școlar. Calitatea formării profesorului pentru comunicare didactică eficientă trebuie să devină parte integrantă și obligatorie în procesul de formare a cadrelor didactice. Aceștia urmăresc să sprijine elevii pentru a reduce riscul abandonului școlar. Profesorii trebuie să devină profesioniști care sunt totdeauna disponibili pentru elevi, ei trebuie să fie deschiși și flexibili în comunicare / relaționare cu elevii și să aibă capacitatea de a rezolva conflictele, de a-i motiva pentru învățare.